2019
DOI: 10.1136/bmjpo-2019-000515
|View full text |Cite
|
Sign up to set email alerts
|

Better Use of Data to improve parent Satisfaction (BUDS): protocol for a prospective before-and-after pilot study employing mixed methods to improve parent experience of neonatal care

Abstract: IntroductionHaving a baby that requires neonatal care is stressful and traumatic. Parents often report dissatisfaction with communication of clinical information. In the UK neonatal care data are recorded daily using electronic patient record systems (EPR), from which deidentified data form the National Neonatal Research Database (NNRD). We aim to evaluate the impact of sharing neonatal EPR data with parents, on parent-reported satisfaction, parent–staff interactions, staff workload and data completeness.Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…This review was conceived in response to the clinical need identified by parents with neonatal care experience; a partnership including families with experience of preterm birth identified ‘what emotional and practical support improves attachment and bonding, and does the provision of such support improve outcomes for premature babies and their families?’ as a top 10 research priority 15. Additionally, this review was conceived as part of planning a wider project to pilot a neonatal intervention, with parents’ full input 16. Patients were not directly involved in the design, conduct, reporting or dissemination plans of our research.…”
Section: Methodsmentioning
confidence: 99%
“…This review was conceived in response to the clinical need identified by parents with neonatal care experience; a partnership including families with experience of preterm birth identified ‘what emotional and practical support improves attachment and bonding, and does the provision of such support improve outcomes for premature babies and their families?’ as a top 10 research priority 15. Additionally, this review was conceived as part of planning a wider project to pilot a neonatal intervention, with parents’ full input 16. Patients were not directly involved in the design, conduct, reporting or dissemination plans of our research.…”
Section: Methodsmentioning
confidence: 99%